2008
DOI: 10.1088/1126-6708/2008/03/021
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of systematical uncertainties for the CP violation measurement in superbeam experiments

Abstract: Superbeam experiments can, in principle, achieve impressive sensitivities for CP violation in neutrino oscillations for large θ 13 . We study how those sensitivities depend on assumptions about systematical uncertainties. We focus on the second phase of T2K, the so-called T2HK experiment, and we explicitly include a near detector in the analysis. Our main result is that even an idealised near detector cannot remove the dependence on systematical uncertainties completely. Thus additional information is required… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 59 publications
1
89
1
Order By: Relevance
“…In this study we are mainly interested in the ν μ → ν e and ν μ → ν μ oscillation modes and their charge conjugated ones. It is useful to write them down in the approximated analytic forms as [17] In these expressions we retain up to the sub-leading terms of 21 , sin 2 θ 13 and aL/4E. The corresponding probabilities for anti-neutrino oscillations can be obtained from the above expressions by reversing the sign of the matter effect term (a → −a) and the CP phase (δ CP → −δ CP ).…”
Section: Neutrino Oscillations In Mattermentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we are mainly interested in the ν μ → ν e and ν μ → ν μ oscillation modes and their charge conjugated ones. It is useful to write them down in the approximated analytic forms as [17] In these expressions we retain up to the sub-leading terms of 21 , sin 2 θ 13 and aL/4E. The corresponding probabilities for anti-neutrino oscillations can be obtained from the above expressions by reversing the sign of the matter effect term (a → −a) and the CP phase (δ CP → −δ CP ).…”
Section: Neutrino Oscillations In Mattermentioning
confidence: 99%
“…The blue (dashed-blue), green (dashed-green), orange (dashedorange) and red curves show the absolute value of the χ 2 MH , Eq. (3.8), for rejecting the wrong mass hierarchy when the ratio of the ν μ andν μ focusing beams is 5:0 (0:5), 4:1 (1:4), 3:2 (2:3) and 2.5:2.5 (×10 21 POT with the proton energy of 40 GeV), respectively. It is shown that includingν μ focusing beam can improve the sensitivity, especially in high sensitivity regions.…”
Section: Sensitivity To the Mass-hierarchy Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…An upgraded beam in the multi-MW range (superbeam) would obviously yield a much better physics potential [7]. However, these beams are eventually limited by intrinsic backgrounds and systematic effects: large flux uncertainties, combined with the inability to measure the final flavor cross sections at the near detector, introduce large systematical errors which are very difficult to control [8,9].For the determination of the CP phase a similar precision to that achieved in the quark sector is only offered by a neutrino factory (NF) [9,10]. In a NF a highly collimated beam of muon neutrinos and electron antineutrinos is produced from muon decays in a storage ring with long straight sections [11].…”
mentioning
confidence: 99%
“…An upgraded beam in the multi-MW range (superbeam) would obviously yield a much better physics potential [7]. However, these beams are eventually limited by intrinsic backgrounds and systematic effects: large flux uncertainties, combined with the inability to measure the final flavor cross sections at the near detector, introduce large systematical errors which are very difficult to control [8,9].…”
mentioning
confidence: 99%